2021
DOI: 10.1101/2021.12.01.470627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A temporal sequence of thalamic activity unfolds at transitions in behavioral arousal state

Abstract: The moment of awakening from sleep reflects a profound transformation in neural activity and behavior. The thalamus is a key controller of arousal state, but whether its diverse nuclei exhibit coordinated or distinct activity at transitions in behavioral arousal state is not known. Using fast fMRI at ultra-high field (7 Tesla), we measured sub-second activity across thalamocortical networks and within nine thalamic nuclei to delineate these dynamics during spontaneous transitions in behavioral arousal state. W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 130 publications
(176 reference statements)
0
4
0
Order By: Relevance
“…Improvements in the temporal resolution of BOLD fMRI have also sparked interest in detecting neural sequences at sub-second timescales, which are highly relevant for many studies of cognition. Recent studies have leveraged fast fMRI to detect rapid sequences of neural events related to visual sequence detection ( Wittkuhn and Schuck, 2021 ), auditory dynamics ( Frühholz et al, 2020 ), and changes in arousal state ( Setzer et al, 2021 ). As we continue to identify these rapid neural sequences, it will become even more crucial to consider how the hemodynamic response varies across regions to determine whether a given sequence represents regional differences in neuronal or in hemodynamic timing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in the temporal resolution of BOLD fMRI have also sparked interest in detecting neural sequences at sub-second timescales, which are highly relevant for many studies of cognition. Recent studies have leveraged fast fMRI to detect rapid sequences of neural events related to visual sequence detection ( Wittkuhn and Schuck, 2021 ), auditory dynamics ( Frühholz et al, 2020 ), and changes in arousal state ( Setzer et al, 2021 ). As we continue to identify these rapid neural sequences, it will become even more crucial to consider how the hemodynamic response varies across regions to determine whether a given sequence represents regional differences in neuronal or in hemodynamic timing.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in acquisition technology now allow high-resolution whole brain fMRI data to be acquired at fast (<500ms) rates ( Polimeni and Lewis, 2021 ; Chen et al, 2019 ; Barth et al, 2016 ; Chiew et al, 2018 ; Hennig et al, 2007 ; Setsompop et al, 2016 ), suggesting that fMRI could provide a unique tool to noninvasively track temporal sequences of neural activity ( Menon et al, 1998 ) across the entire brain. Indeed, recent studies have revealed highly structured temporal dynamics using fMRI and suggest that fMRI can enable whole-brain mapping of temporal sequences ( Lee et al, 2013 ; Setzer et al, 2021 ; Raut et al, 2021 ; Mitra et al, 2016 ; Vizioli et al, 2018 ). Furthermore, hemodynamic signals have been shown to contain more information about fast and high-frequency activity than previously thought ( Lee et al, 2013 ; Smith et al, 2012 ; Chen and Glover, 2015 ; Lewis et al, 2016 ; Sasai et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in the temporal resolution of BOLD fMRI have also sparked interest in detecting neural sequences at sub-second timescales, which are highly relevant for many studies of cognition. Recent studies have leveraged fast fMRI to detect rapid sequences of neural events related to visual sequence detection (76), auditory dynamics (77), and changes in arousal state (22). As we continue to identify these rapid neural sequences, it will become even more crucial to consider how the hemodynamic response varies across regions to determine whether a given sequence represents regional differences in neuronal or in hemodynamic timing.…”
Section: Discussionmentioning
confidence: 99%
“…pattern of BOLD activity propagates across the thalamus with fluctuating arousal(Gu et al, 2021;Raut et al, 2021;Setzer et al, 2021), which is a core deep-brain structure comprised of sub-nuclei with diverse functional roles in cognition. Therefore, slow, rhythmic brain dynamics have some functional and spatial structure.…”
mentioning
confidence: 99%